Clinicoepidemiological profile of childhood leprosy in Western Odisha: A retrospective, hospital-based study - Swetalina Pradhan; Bibhu Prasad Nayak; Tanmay Padhi; Kananbala Sahu (Wolters Kluwer Medknow Publications, 2020)
Background: At this postelimination era, childhood leprosy is still a major concern for the society. Studies regarding the clinicoepidemiological profile of childhood leprosy from Western Odisha are unavailable despite the area being endemic to leprosy. Aim and Objective: The aim and objective was to study the clinicoepidemiological profile of childhood leprosy in Western Odisha. Materials and Methods: Patients aged <18 years with a clinical diagnosis of Hansen's disease were included in the study. Data regarding demographic profile, type of Hansen's disease, family history of Hansen's disease, various types of deformities, lepra reactions, treatment status, and any side effects of treatment were collected from the leprosy register and proformas. Results: Out of the total 1460 leprosy patients, 239 (16.4%) patients were children. The mean age of the patients was 13.43 ± 1.09 years. Borderline tuberculoid leprosy was the most common type of presentation (141 cases). Family contacts were identified in 33.2% of cases, with majority being multibacillary. Disabilities and lepra reactions were found in 9.3% and 19.2% of children, respectively. Mononeuritis was found in 141 (59%) patients. Ulnar nerve was the most commonly involved nerve in 97 (67.8%) cases, followed by common peroneal nerve in 44 (31.2%) cases in patients with mononeuritis. Out of 98 patients presenting with polyneuritis, ulnar nerve was the most common nerve enlarged clinically in 66 (67.3%) patients followed by common peroneal in 51 (52.04%), great auricular in 7 (7.14%), radial cutaneous nerve in 5 (5.1%), sural in 4 (4.1%), posterior tibial in 3 (3.1%), and superficial peroneal in 1 (1.02%) patients. Out of 239 cases, 11 had completed treatment, 37 cases were continuing treatment from outside, and 191 new cases (13.1%) had started treatment. At the end of 2 years, a total of 157 cases had completed treatment and the rest were continuing treatment. No defaulter and relapse case were found within the 2-year period. Side effect profile of antileprosy treatment was available in 47 patients with dapsone hypersensitivity syndrome in 2 cases, maculopapular drug reaction in 5 cases, and clofazimine-induced pigmentation in all. Conclusion: Higher proportion of childhood leprosy indicates transmission of leprosy in Western Odisha. Clustering of multibacillary cases in family suggests that family contact tracing is mandatory in all cases. Though less commonly found, physicians should be aware of the side effects of antileprosy treatment and counseling should be done regarding the side effect profile while initiating treatment.